The effect of telework on emotional exhaustion and task performance via work overload: The moderating role of self-leadership - Junça Silva, A.; Almeida, A.; Rebelo, C. (International Journal of Manpower, 2024)
This study developed a framework that explains how and when telework is related to emotional exhaustion and task performance, by conceiving work overload as a mediator and self-leadership as a moderator. We conducted two studies. Study 1 aimed to understand whether telework would be related to emotional exhaustion and task performance and if work overload would mediate such relationships. Study 2 analyzed whether self-leadership was a significant moderator of the mediated relations found in Study 1. The hypotheses were tested in a sample of 207 (in Study 1) and 272 (in Study 2) participants, that were exclusively teleworking. The results were analyzed using PROCESS macro in SPSS. The results of study 1 showed that telework dimensions were negatively related to work overload, which consequently decreased emotional exhaustion and increased task performance. In Study 2, self-leadership moderated the indirect effect of work overload on the relationship between telework and emotional exhaustion, such that the indirect effect was stronger for those who scored higher in self-leadership. However, it was not significant for task performance. This paper adds to research on telework by focusing on the employee’s mental health and performance, in the context of mandatory confinement. The authors identified telework dimensions that may act as resources to cope with the increased work overload inherent to telework, as well as the importance of personal resources in these relationships.